2020
DOI: 10.3389/fonc.2020.608548
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool to Predict Early Death in Uterine Sarcoma Patients: A Surveillance, Epidemiology, and End Results-Based Study

Abstract: BackgroundUterine sarcoma is a rare gynecologic tumor with a high degree of malignancy. There is a lack of effective prognostic tools to predict early death of uterine sarcoma.MethodsData on patients with uterine sarcoma registered between 2004 and 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) data. Important independent prognostic factors were identified by univariate and multivariate logistic regression analyses to construct a nomogram for total early deaths and cancer-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This implies that stage is an important independent in uencing factor. This is consistent with the results of previous studies on prognostic evaluation models for pancreatic cancer and uterine sarcoma 13,14 . The prognosis of stage III and IV patients is generally poor and mainly depends on the size of intraperitoneal metastases 15 .…”
Section: Discussionsupporting
confidence: 93%
“…This implies that stage is an important independent in uencing factor. This is consistent with the results of previous studies on prognostic evaluation models for pancreatic cancer and uterine sarcoma 13,14 . The prognosis of stage III and IV patients is generally poor and mainly depends on the size of intraperitoneal metastases 15 .…”
Section: Discussionsupporting
confidence: 93%
“…The study on early death has been applied to advanced cancers in other systems and has shown important clinical significance. Song et al established a nomogram chart to predict the early mortality of uterine sarcoma, which was significantly better than FIGO stage system [ 24 ]. Yang et al established a model to predict the early mortality of stage IV gastric cancer, and the AUC was as high as 0.847 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 illustrates a flowchart of patient selection. According to past research ( 8 , 9 ), death within 3 months of initial diagnosis was defined as early death.…”
Section: Methodsmentioning
confidence: 99%